Pengaruh Earplug dan Eye Mask terhadap Kualitas Tidur pada Pasien dengan Gangguan Tidur di Intensive Care unit - Tinto Riza Pahlevi; Musaddad Kamal; Ani Haryani; Al Ayubi (Faletehan Health Journal, 2025)
Sleep disturbances, such as noise and light, can affect metabolism and inflammatory processes of ICU patients, negatively impacting on health. This study aimed to determine the effect of using earplugs and eye masks in improving sleep quality of ICU patients. The method used was quantitative with a quasy experimental non-equivalent group control design. The number of samples was 28 respondents who were selected by purposive sampling technique and divided into 2 groups. The sleep quality instrument used the Richard Campbell Sleep Questionnaire (RCSQ). Data were analyzed by frequency distribution test, Independent Sample T-Test and paired sample T-Test through SPSS version 25. The results of this study showed that there was a significant effect before and after the use of earplugs and eye masks. Although the use of earplugs and eye masks is a cost-effective, safe, and can improve the sleep quality of ICU patients, further research is needed to identify the effect of these interventions on certain disease groups.